Sars-CoV2- infection as a trigger of humoral response against apolipoprotein A-1. (14th October 2021) - Pagano, S; Yerly, S; Suh, N; Le Terrier, C; Farrera-Soler, L; Piumatti, G; Eberhardt, C S; Siegrist, C A; Eckerle, I; Stringhini, S; Guessous, I; Kaiser, L; et al.
Abstract: Background: Unravelling autoimmune targets triggered by SARS-CoV-2 infection may provide crucial insights in the physiopathology of the disease and foster the development of potential therapeutic candidate targets and prognostic tools. SARS-CoV-2 autoimmune-mediated inflammation have been reported, but the existence of autoantibodies against apolipoprotein A-1 (anti-apoA-1 IgG) in COVID-19 remains unexplored. Anti-apoA-1 IgGs have emerged as an independent biomarker for cardiovascular disease and mortality in humans with proinflammatory and proatherogenic functions in vivo and in vitro. Purpose: We want to determine i) the degree of homology between SARS-CoV-2, apoA-1, and Toll-like receptor-2 (TLR2) epitopes, ii) the association between anti-SARSCoV2 and anti-apoA-1 IgGs, and iii) their relationship to prognosis. Methods: We performed bioinformatics modelling coupled with mimetic peptides engineering, as well as functional and competition assays with antibodies to identify molecular mimicry between SARS-CoV-2, apoA-1 and TLR2 epitopes. Anti-Spike domain 1 (SD1) IgGs, anti-apoA-1 IgGs and against mimic peptides, as well as cytokines were assessed by immunoassays on a case-control (n=101), an intensive care unit (ICU; n=126) with a 28-days follow-up for overall mortality, and a general population cohort (n=663) with available samples in the pre and post-pandemic period. Results: Linear sequence homologies and antibodies cross-reactivity between apoA-1, TLR2, and Spike epitopes were identified. Overall, anti-apoA-1 IgG levels were higher in COVID-19 patients or anti-SARS-CoV-2 seropositive individuals than in healthy donors or anti-SARS-CoV-2 seronegative individuals (p<0.0001). Significant and similar associations were noted between anti-apoA-1, anti-SARS-CoV-2 IgG, cytokines, and lipid profile. In ICU patients, anti-SARS-CoV-2 and anti-apoA-1 seroconversion rates displayed similar 7-days kinetics, reaching 82% for anti-apoA-1 seropositivity. C-statistics (CS) indicated that baseline anti-Spike/TLR2 mimic-peptide IgGs displayed a significant prognostic accuracy for overall mortality at 28 days (CS: 0.64; p=0.02). In the general population, SARS-CoV-2 exposure increased baseline anti-apoA-1 IgG levels. Conclusions: COVID-19 induces a marked humoral response against the major protein of high-density lipoproteins. As a correlate of poorer prognosis in other clinical settings, such autoimmunity signatures may relate to long-term COVID-19 prognosis assessment and warrant further scrutiny in the current COVID-19 pandemic. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): This study was funded by the Swiss Federal Office of Public Health, Swiss School of Public Health (Corona Immunitas research program), the Fondation de Bienfaisance du Groupe Pictet, the Fondation Ancrage, the Fondation Privée des HUG, and the Center for Emerging Viral Diseases. The De Reuter (grant Nr 657) and the Schmidheiny Foundation.